Visualization and Study Mode Architectures for Real-Time Power System Control - Grijalva Silva, Carlos Santiago (2007)
This paper describes the architecture of Retriever, an innovative system for power system control centers, which provides advanced visualization and study mode features. Visual monitoring has many advantages over traditional non-graphic supervision, allowing the operator to process large amounts of information and capture the aspects relevant to prevent insecure power system states in a very efficient manner. Real-time power flow and study mode simulations allow the discovery of potential problems in the system and points out towards prompt control actions by the operator. Theses visualization and analysis tools have been integrated to provide a powerful architecture for real-time power system monitoring, and are operative in large control centers with tenths of thousands of nodes.